Application of The Methaporical Thinking Method to Improve The Ability of Mathematical Connections, Creative Thinking and Self Confidence of Vocational School Students - Ahmad Mirza (IKIP Siliwangi, 2020)
This study aims to examine the improvement of mathematical connection skills and creative thinking as well as students' self confidence. This is in line with the problems in this study, namely the low ability of mathematical connections and the ability to think creatively as well as the self-confidence of SMK students. This quasi-experimental study took a population of all students of SMK Negeri 1 Campaka, Cianjur Regency, with a sample of class XI, the class was given a pretest and posttest for mathematical connection skills and students' creative thinking abilities. The results of the quantitative data analysis research using the SPSS.19 for windows application program, show that based on the learning model and the cognitive stage, the level of achievement and increased mathematical connection skills and mathematical creative thinking of students who use the method of methaporical thinking is better than students who use conventional learning.